2015
DOI: 10.18632/oncotarget.5500
|View full text |Cite
|
Sign up to set email alerts
|

Novel RNA variants in colorectal cancers

Abstract: With an annual estimated incidence of 1.4 million, and a five-year survival rate of 60%, colorectal cancer (CRC) is a major clinical burden. To identify novel RNA variants in CRC, we analyzed exon-level microarray expression data from a cohort of 202 CRCs. We nominated 25 genes with increased expression of their 3′ parts in at least one cancer sample each. To efficiently investigate underlying transcript structures, we developed an approach using rapid amplification of cDNA ends followed by high throughput seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Recently, the importance of CASZ1 in tumorigenesis is becoming increasingly recognized. Aberrant fusion transcript of CASZ1 has been reported in colorectal cancer [ 18 ] and bladder cancer [ 19 ]. CASZ1 is downregulated and functions as a crucial tumor suppressor in neuroblastoma [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the importance of CASZ1 in tumorigenesis is becoming increasingly recognized. Aberrant fusion transcript of CASZ1 has been reported in colorectal cancer [ 18 ] and bladder cancer [ 19 ]. CASZ1 is downregulated and functions as a crucial tumor suppressor in neuroblastoma [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some potential biomarkers in cancers have been identified based on exon microarray or NGS. For example, through the combination of exon microarray and RNA sequencing (RNA-Seq), Hoff et al found that the fusion of VWA2-TCF7L2, DHX35-BPIFA2, and CASZ1-MASP2, as well as some novel transcript structures, may play an important role in CRC [ 13 ]. Compared with NGS, microarray has some obvious shortcomings, including the fact that it cannot detect unknown alterations of genomic structure that might contribute to progression of cancers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A clinical case report showed that CASZ1 gene expression was disrupted as a consequence of human papillomavirus DNA integration into the CASZ1 gene locus in a case of cervical cancer (10). In colorectal cancer, CASZ1 and MASP2 fusion transcript was detected, and this fusion product encodes a N-terminal truncated MASP2 that under the control of CASZ1 promoter (11). Our studies have shown that the CASZ1 gene is silenced in poor prognosis neuroblastoma (NB) patient tumor samples through loss of heterozygosity and/or EZH2-mediated epigenetic silencing (12).…”
Section: Introductionmentioning
confidence: 99%